The Role of Professional Child TV Journalists in the Production of Animated Programs for Preschoolers: Experiences from Kazakhstan and Kyrgyzstan - Sabyr, А.Б.; Koshkenov, Н.Ж.; Ryskeldinova, С.Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
The article analyzes the transformation of professional roles and functions of a children’s television journalist in the context of integrating generative artificial intelligence and Lean Animation methodology. Using the experimental project “Tobetai” as a case study, the research explores the adaptation of editorial activities to new technological challenges in the media landscape of Kazakhstan and Kyrgyzstan, as well as mechanisms for preserving cultural codes in digital content. The study is based on a comparative analysis of content from national children’s channels “Balapan” and “Balastan,” along with the participant observation method within the production cycle of an animated series. Psycholinguistic methods for assessing the cognitive accessibility of text (TTR, MLU), visual-semiotic analysis, and mathematical modeling of production efficiency within the Lean concept were applied. The authors identify and theoretically substantiate a new typology of professional roles: the journalist as a software engineer, axiological curator, and ethnic editor. It is proven that the Lean Animation model allows for a 3.2-fold reduction in production costs while maintaining a high level of ethnocultural authenticity and visual safety. It is established that in modern animation, a journalist assumes the functions of a “media environment architect,” performing multi-layered validation of ethical and linguistic parameters for content targeting children aged 3–4. The conclusions and the proposed production model can be implemented into the practice of national television channels to accelerate import substitution and strengthen cultural sovereignty amidst global competition. The findings are valuable for modernizing journalism curricula and professional development programs for media managers.